Study Of Ethnomedicinal Plants Used By The Local People Of Feni District, Bangladesh - Uddin, Mohammad Zashim; Kibria, Md Golam; Hassan, Md Abul (Journal of the Asiatic Society of Bangladesh, Science, 2015)
Ethno-medicinal study was conducted to document medicinal plants used by the local people of Feni district. The targets of the study were to identify and document plant species used for treatment of various ailments and to find out the level of consensus or agreement between informants regarding the uses of plants for particular disease categories. The study has been resulted in recording of 115 medicinal plant species with 216 formularies to treat 69 ailments. These species belongs to 5 5 families. Such data indicated that the study area has plenty of medicinal plants with their diversity of health care uses. Ailment category cut and wounds attained highest Fic value. Species used for this purpose are Mikania cordata, and Cynodon dactylon which were cited by many informants. Second highest Fic value was found in case of Dysentery and diarrhoea. Medicinal plants used for this purpose are Litsea glutinosa, Dalbergia sissu, Mangifera indica, Scoparia dulcis, Holarrhena antidysenterica, Stephania harnandifolia and Centella asiatica those were cited by a good number of informants. Since the Fic values attained highest, such plants could be recommended for further phytochemical study to isolate compounds responsible for the remedy of ailment category cut and wounds and diarrhoea and dysentery. In the present survey, 1 6 species has attained 100% FI values. This FI values means that the informants have a tendency to rely on one specific plant species for treating one certain ailment than several ailments. The study asserted that such species need to be protected in the study area to sustain traditional medicinal plants and culture. Finally, a number of threats to the medicinal plants have been identified and some measures for conservation have been suggested. Asiat. Soc. Bangladesh, Sci. 41(2): 203-223, December 2015